Party formation and policy outcomes under different electoral systems - Massimo Morelli (Fondazione Eni Enrico Mattei (FEEM), 1998)
This paper provides a game-theoretic model of representative democracy with endogenous party formation. Coalition formation may occur before and after elections, and the expected payoffs from the after-election majority game affect incentives to form parties before the elections. In this way Duverger's hypothesis can be formally explained by the strategic behaviour of political elites. If politicians care primarily about private benefits, the equilibrium policy outcome under a proportional electoral system coincides with the median party's position. On the othoer hand, with quasilinear utility, the distance from the median voter outcome may be lower with plurality rule.
Keywords: C7; D72; 330; Party formation; Electoral systems; Majoritarian bargaining; Representative democracy; Regierungskoalition; Wahlsystem; Ökonomische Theorie der Demokratie; Spieltheorie; Theorie